THE IMPACT OF THE CLIMATE CHANGE ON WATER, FLOOD AND DAN EROSION CYCLE IN UPPER CITARUM HULU UDING MODELING - Shantosa Yudha Siswanto; Riskha Mardiana (Prosiding Sains dan Teknologi, 2026)
The Cikeruh, Citarik, and Cirasea sub-watersheds are part of the Citarum watershed which is included in the 15 priority watersheds for critical land recovery. One of the causes of land criticality is the conversion of land use that is not in accordance with the capabilities of the available land. The purpose of this study was to determine land use conversion that occurred in the Cikeruh, Citarik, and Cirasea Sub-watersheds during 1990-2015 and to predict land use conditions in the research area in 2029. This research was conducted through a descriptive quantitative analysis approach through the interpretation of Landsat 5 TM and Landsat 8 OLI satellite imagery supervised classification methods with the maximum likelihood algorithm and Utilization of the IDRISI application, Land Change Modeler (LCM) for predictive modeling of future land use . The types of use of built-up land, paddy fields and open land are predicted to increase by 3,761.26 Ha (29.02%), 441.10 Ha (4.84%), 267.04 Ha (4.55%), respectively.